An Empirical Analysis of Heat Expulsion and Pressure Drop Attribute in Helical Coil Tube Using Nanomaterials. (16th May 2022) - Algarni, Salem; Tirth, Vineet; Alqahtani, Talal; Kshirsagar, Pravin R.; Abera, Worku
Abstract : Water nanofluids were examined in a horizontal helical coil tube with constant temperature limitations for Dean values between 1000 and 10, 000 to determine the rate of thermal radiation transmission and pressure drop characteristics. When conducting the tests, a variety of Al2 O3 water nanofluid requirements were used, including varying mass flows, heat exchange rates for various nanoparticle volume concentrations, and changes in coil-side drop in pressure versus coil-side Dean number. Since nanoparticles have enhanced heat capacity, nanoparticles are developing as a transitional beginning of heat transfer fluids with significant potential in thermal management applications. Many applications require nanofluids to be used as heat transfer fluids; thus, scientists are concentrating their efforts on these fluids. The Reynolds values on the coil and shell were in the 1000 to 7000 range on either side of the wire. This paper discusses the impact of particle volume density on shell-side flow temperatures, heat expulsion rate, and thermal conduction. The result shows that the average heat transfer rises by 13% and 17% when nanoparticle volume fraction percentage density is 0.1%, 0.2%, and 0.3 percent. The results demonstrate that reducing the mass flow by an increase in particle volume density, pipe diameter, and coil radius improves heat exchanger performance. The efficiency of the model is enhanced by increasing the diameter of the tube while simultaneously decreasing the diameter of the coil.